PANTUN DAN IDENTITAS MASYARAKAT MELAYU PONTIANAK - Putri, Sintya Dewi; Effendy, Chairil; Seli, Sesillia (Universitas Tanjungpura, 2023)
This study aims to interpret the structure of the pantun and the identity of the Malay community in the Pontianak Malay pantun into the form of a draft Indonesian language learning plan. The research method used is descriptive in the form of qualitative research. The data source of this research is the Pontianak Malay pantun spoken by the rhyme speaker. The results showed that first, the characteristics of the rhyme consisted of; each stanza consists of four lines, rhythmic ab ab, one line usually consists of four to six words (eight to twelve syllables) or even, the first two lines are sampiran, the next two lines are content. The contents can be in the form of advice, customs, religion, young people such as love and love. Pantun also has two main structures, namely the inner and physical structures. One of the physical structures that are not included in the rhyme data is figurative language (figure of speech). Second, the language used by the Pontianak Malay community is Malay, so most of the Pontianak Malay pantun use the Pontianak Malay language. Malay rhymes are used in various places and in various social conditions. Besides that, it is also used in communicating, teaching, for entertainment and to shape the identity of the Pontianak Malay community. The Malay rhymes used are not bound by age, gender, social stratification, and blood relations.